PENERAPAN MODEL PEMBELAJARAN KOOPERATIF STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) DALAM UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA MATERI HIMPUNAN SISWA KELAS VII1 SMP NEGERI 15 KENDARI - Farman _; Chairuddin _; Fitriyani Hali (Jurnal Karya Pendidikan Matematika, 2019)
This research aims to improve mathematics learning outcomes of students of grade VII1 SMP Negeri 15 Kendari on set material through the application of the Student Teams Achievement Division (STAD) learning model. This type of research is Classroom Action Research (CAR). This research was conducted in class VII1 students of SMP Negeri 15 Kendari with 24 students. The results of this study indicate that the completeness of student learning outcomes in the first cycle reached 70.83%, in the second cycle reached 79.16%, and in the third cycle reached 83.3%. In terms of process, the Student Teams Achievement Division (STAD) cooperative learning model has been implemented in accordance with the learning scenario in class VII1 of SMP Negeri 15 Kendari with an average of 75% in cycle I, 85% in cycle II and 95% in cycle III. Based on the performance indicators, it was concluded that student learning outcomes in the material set of students in class VII1 of SMP Negeri 15 Kendari could be improved through the cooperative learning model of Student Teams Achievement Division (STAD).